Typical Meteorological Year Data: SolarGIS Approach. (May 2015) - Cebecauer, T.; Suri, M.
Abstract: We analyze factors to be considered when Typical Meteorological Year (TMY) is constructed from a time series data. We discuss characteristics of the input data (time period, time frequency, quality), calculation methods (weighting of parameters, coherence of parameters, selection criteria) and requirements of the resulting TMY to characterize average solar climate (P50 case) or a year with less-favorable solar resource (P90 or Pxx cases). Overview of the existing methods is presented, with summary of their features, limitations and associated risks. SolarGIS method is presented, which overcomes limitations of the older methods. We explain the underlying concept of uncertainty that is used for calculation of annual P90 or Pxx values for Direct Normal Irradiation (DNI) and Global Horizontal Irradiation (GHI). SolarGIS method fulfills the criteria required in solar industry, such as geographical representativeness, consistency of solar radiation and meteorological parameters, and yields a good representation of the P50, P90 or any other Pxx cases.